A Scoping Review of Risk Factors for Intimate Partner Violence Perpetrators in Indonesia - Vidyadhara, Kalista; Pertiwi, Pradytia Putri (Buletin Psikologi, 2024)
Intimate partners are reported by the National Commission on Violence Against Women to be the primary perpetrators of sexual violence. However, the government has limited its perpetrator-focused intervention to enforcing the law. Meanwhile, there has been a growing interest in understanding Intimate Partner Violence (IPV) ecologically and developing interventions that go beyond punishing the perpetrators. This systematic literature review aimed to explore the risk factors of IPV perpetrators in Indonesia. There were 3309 articles generated from databases. Five articles were included, and the result confirms the scarcity of Indonesian papers on: (1) the usage of the IPV term; (2) the exploration of IPV perpetrator risk factors; and (3) the poor quality of existing research on IPV. It is evident within the five articles that individual and societal risk factors are interconnected in Indonesia. Recommendations are threefold: (1) researchers are recommended to employ the term IPV, include couples despite their marital status, and explore risk factors of IPV perpetrators; (2) clinicians are suggested to adopt the ecological framework and collaborate with government and non-government institutions to advocate the importance of perpetrator-focused interventions; (3) institutions are suggested to design preventive measures according to the ecological model.